O SINCRETISMO ENTRE AS SEMIÓTICAS VERBAL E VISUAL - Pietroforte, Antonio Vicente Seraphim (2010)
Studying the plane of expression based on the theory of semi-symbolism, the Semiotics studies the syncretism. Our work explores the meaning effects between verbal and visual, based on the models proposed by J. M. Floch and R. Barthes about the rhetoric of image.